A metal / metal oxide composite catalyst and its preparation method and application
Through the preparation of metal/metal oxide composite catalyst, the synergistic effect of transition metal element and oxide is used to solve the problem of poor agglomeration and dispersion of catalysts during hydrogenation, the hydrogen absorption and release performance of hydrogen storage materials is improved, and high efficiency is achieved Catalytic effect.
Patent Information
- Application Number
- CN202310876998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-07-18
AI Technical Summary
Existing metal elementary catalysts are prone to agglomeration during hydrogenation, have poor dispersion and low catalytic activity, making it difficult to improve the hydrogen absorption and discharge performance of hydrogen storage materials.
Using metal/metal oxide composite catalyst, nanocomposite particles are prepared by controlling the mass ratio of transition metal element and oxide and the content of the supported material, and hydrothermal reaction and heat treatment technology are used to ensure the dispersion and catalytic activity of the particles.
The hydrogen storage performance of hydrogen storage materials is improved, the excellent characteristics of the supported materials and the coordinated catalytic properties of transition metal elements and oxides are achieved, and the prepared catalyst has good dispersion and efficient catalytic activity.
Smart Images

Figure CN116870916B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a metal / metal oxide composite catalyst and a preparation method and application thereof. Background Art
[0002] As society's demand for energy continues to expand, my country's energy supply and demand are becoming increasingly tight. Hydrogen energy has attracted much attention due to its large reserves, cleanliness, and high efficiency. Hydrogen storage materials are important carriers for hydrogen storage and transportation, and how to improve the hydrogen storage performance of materials has become a research focus.
[0003] Catalysts are an important means to improve the hydrogen absorption and desorption performance of hydrogen storage materials (such as magnesium hydride materials). Their particle size and particle distribution have a great influence on the catalytic activity. Common catalysts include transition metal elements and their oxides, sulfides or halides, and nickel elements have attracted much attention due to their low cost and high efficiency. However, during the preparation of catalysts and the absorption and desorption of hydrogen by hydrogen storage materials, nickel particles are prone to agglomeration and growth, and have poor dispersion performance, which seriously reduces the catalytic activity of nickel particles. Therefore, it is very necessary to study catalysts with simple preparation methods, high activity, good dispersion performance and stable structure. Summary of the invention
[0004] Based on this, the embodiments of the present invention provide a metal / metal oxide composite catalyst and a preparation method and application thereof, aiming to solve the problems of existing single metal catalysts being easy to agglomerate, having low dispersion uniformity, and having low catalytic activity during hydrogen absorption and desorption.
[0005] To achieve the above-mentioned purpose, on the one hand, an embodiment of the present invention provides a metal / metal oxide composite catalyst, comprising a support material and composite particles supported on the support material; the composite particles are particles made of a transition metal element and a transition metal oxide; based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the support material is 10% to 80%, the mass percentage of the transition metal element is 10% to 45%, and the mass percentage of the transition metal oxide is 10% to 45%.
[0006] According to the actual use needs, the mass percentage of the supported material can be 10%, or 20%, or 30%, or 40%, or 50%, or 60%, or 70%, or 80%, etc. The mass percentage of the transition metal element can be 10%, or 15%, or 20%, or 25%, or 30%, or 35%, or 40%, or 45%, etc. The mass percentage of the transition metal oxide can be 10%, or 15%, or 20%, or 25%, or 30%, or 35%, or 40%, or 45%, etc. If the content of the supported material is too high, the catalytic effect of the composite catalyst will be reduced; if the content of the supported material is too low, it will not play a good role in supporting the composite particles, which will affect the size and dispersibility of the composite catalyst particles and reduce its catalytic activity.
[0007] As a preferred embodiment, based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the supported material is 40%, the mass percentage of the transition metal element is 30%, and the mass percentage of the transition metal oxide is 30%.
[0008] As a preferred embodiment, the mass ratio of the transition metal element to the transition metal oxide is (1-3):(1-3); the ratio of the sum of the masses of the transition metal element and the transition metal oxide to the mass of the support material is (0.5-9):1.
[0009] According to the actual use requirements, the mass ratio of transition metal element and transition metal oxide can be 1:3, or 2:3, or 3:1, or 1:1, etc. The ratio of the sum of the mass of transition metal element and transition metal oxide to the mass of the load material can be 0.5:1, or 3:1, or 6:1, or 8:1, or 9:1, etc.
[0010] By controlling the mass ratio of transition metal elements and transition metal oxides, and the mass ratio of transition metal elements and transition metal oxides to load materials, the synergistic effect between transition metal elements and transition metal oxides can be well exerted, and the hydrogen storage performance of hydrogen storage materials can be greatly improved through the synergistic effect between transition metal elements and transition metal oxides.
[0011] As a preferred embodiment, the load material is few-layer graphene or carbon; the transition metal element is metal nickel (Ni); the transition metal oxide is scandium trioxide (Sc2O3); and the composite particles are nanocomposite particles.
[0012] On the other hand, an embodiment of the present invention also provides a method for preparing the metal / metal oxide composite catalyst, comprising the following steps:
[0013] SO1, adding a transition metal element source and a transition metal oxide source to an organic solvent, stirring until dissolved, to obtain a first mixed solution; adding urea to the first mixed solution, stirring until dissolved, to obtain a second mixed solution;
[0014] SO2, adding ammonium fluoride (NH4F) and a supporting material to the second mixed solution, stirring evenly to obtain a third mixed solution;
[0015] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing it, drying it, then subjecting it to a heat treatment, and cooling it to obtain a metal / metal oxide composite catalyst;
[0016] Taking the mass of the metal / metal oxide composite catalyst as 100%, the mass percentage of the supported material is 10% to 80%, the mass percentage of the transition metal element is 10% to 45%, and the mass percentage of the transition metal oxide is 10% to 45%.
[0017] As a preferred embodiment, in step SO1,
[0018] 0.8724 g of nickel source was added to every 50 ml of organic solvent; the mass ratio of the nickel source to the urea was 1.2105:1.
[0019] The transition metal element source is nickel nitrate hexahydrate, preferably nickel nitrate hexahydrate with crystal water.
[0020] The transition metal oxide source is hydrated scandium nitrate, preferably hydrated scandium nitrate with crystal water.
[0021] The organic solvent is methanol.
[0022] The stirring is magnetic stirring; the stirring time is 20min to 60min.
[0023] As a preferred embodiment, in step SO2,
[0024] The mass ratio of the ammonium fluoride to the support material is 1:(1.649-4.406).
[0025] The support material is few-layer graphene (FLG) or carbon.
[0026] The stirring is magnetic stirring; the stirring time is 20min to 60min.
[0027] As a preferred embodiment, in step SO3,
[0028] The temperature of the hydrothermal reaction is 100° C. to 180° C., preferably 120° C.; the time of the hydrothermal reaction is 5 h to 15 h, preferably 8 h.
[0029] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0030] The centrifugal speed is 5000r / min to 8000r / min (depending on the actual use needs, it can be set to 5000r / min, or 6000r / min, or 7000r / min, or 8000r / min, etc.), and the centrifugal time is 5min to 20min (depending on the actual use needs, it can be set to 5min, or 10min, or 15min, or 20min, etc.).
[0031] The drying temperature is 50° C. to 80° C., and the drying time is 20 h to 48 h.
[0032] The heat treatment temperature is 400°C to 800°C (depending on the actual use needs, it can be set to 400°C, 500°C, 600°C, 700°C, 800°C, etc.), preferably 500°C to 550°C; the heat treatment time is 0.5h to 5h, preferably 1h to 2h.
[0033] If the heat treatment temperature is too low, the transition metal oxide (scandium trioxide) cannot be generated; if the heat treatment temperature is too high, the transition metal single substance (nickel) particles will crystallize and grow rapidly, reducing its catalytic activity. If the heat treatment time is too long, the catalyst grains will grow, reducing the catalytic activity of the catalyst, and further reducing the hydrogen storage performance of the composite material; if the heat treatment time is too short, it is not conducive to the formation of nanocomposite particles.
[0034] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0035] On the other hand, the embodiments of the present invention also provide applications of the metal / metal oxide composite catalyst, which can be used in hydrogen storage materials, hydrolysis hydrogen production materials, battery materials, supercapacitors and photoelectric materials.
[0036] As a preferred embodiment, the hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal / metal oxide composite catalyst.
[0037] As a preferred embodiment, based on the mass of the magnesium-based composite hydrogen storage material being 100%, the magnesium-based composite hydrogen storage material is prepared from 80% to 99% of magnesium hydride and 1% to 20% of the metal / metal oxide composite catalyst.
[0038] As a preferred embodiment, based on the mass of the magnesium-based composite hydrogen storage material being 100%, the magnesium-based composite hydrogen storage material is prepared from 92% magnesium hydride and 8% of the metal / metal oxide composite catalyst.
[0039] As a preferred embodiment, the magnesium hydride is magnesium hydride powder with a purity greater than 99% and a powder particle size less than 50 μm.
[0040] As a preferred embodiment, the preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 80% to 99% of magnesium hydride and 1% to 20% of the metal / metal oxide composite catalyst to obtain a mixed powder; and ball milling the mixed powder to obtain a magnesium-based composite hydrogen storage material.
[0041] As a preferred embodiment, the ball-to-material ratio of the ball mill is (10-50):1; the ball milling time is 1h-10h, preferably 2h-4h; the ball milling speed is 200r / min-500r / min (for example, it can be 400r / min).
[0042] As a preferred embodiment, the ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.
[0043] In the embodiments of the present application, there is a good synergistic effect between the transition metal element and the transition metal oxide, and the synergistic effect between the transition metal element and the transition metal oxide can greatly improve the hydrogen storage performance of the hydrogen storage material.
[0044] Taking transition metal element nickel and transition metal oxide scandium trioxide as examples, the synergistic effect of the two on the hydrogen storage performance of hydrogen storage materials is explained: Due to the high hardness of scandium trioxide, the composite nanoparticles can destroy the MgO oxide layer on the surface of MgH2, thereby embedding into MgH2, allowing Ni and Sc2O3 to directly contact MgH2 and exert a better catalytic effect. During the dehydrogenation process, Ni and Mg undergo an alloying reaction to form a Mg2Ni phase, and part of Sc 3+ After being reduced to Sc0, Sc0 still exists stably after absorbing hydrogen, which can destabilize the Mg-H bond. After the Sc2O3 particles wrapped on the surface of Ni particles are compounded with MgH2, the Sc2O3 particles are embedded between the Ni particles and MgH2, which can effectively prevent Ni from segregating during the alloying reaction, thereby maintaining Ni's efficient catalytic activity.
[0045] Compared with the prior art, the embodiments of the present invention have the following technical effects:
[0046] (1) The composite catalyst of the present application not only has the excellent properties of the support material, but also has the excellent catalytic performance of the transition metal element and the transition metal oxide. The composite nanoparticles (small particle size, about 20nm) are prepared by wrapping the transition metal oxide particles on the surface of the transition metal element particles, and the composite nanoparticles are supported on the support material, and the composite nanoparticles have good dispersibility on the support material; the support material and the transition metal element are connected by chemical bonds (Ni-C bonds), and the connection is firm, and will not be separated from the composite nanoparticles due to washing or ultrasonic treatment; there is a good synergistic effect between the transition metal element and the transition metal oxide, which can greatly improve the hydrogen storage performance of the hydrogen storage material.
[0047] (2) The raw materials of the present application are easily available and inexpensive, the preparation method is simple, easy to operate, and the experimental cycle is short, the controllability is good, and it is easy to mass produce. The present invention uses urea as a precipitant and ammonium fluoride as a nucleating agent and controls their proportion and dosage, adopts a liquid phase method, and prepares the composite catalyst by coprecipitation, which is conducive to the uniform distribution of the catalyst components and can further improve the synergistic catalytic performance between the transition metal element and the transition metal oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0049] Figure 1 The X-ray diffraction (XRD) pattern of the metal / metal oxide composite catalyst (i.e., few-layer graphene-supported Ni / Sc2O3 composite nanoparticles) of Example 2;
[0050] Figure 2 This is a FESEM image of the few-layer graphene-supported Ni / Sc2O3 composite nanoparticles of Example 2;
[0051] Figure 3 TEM and EDS images of the few-layer graphene-supported Ni / Sc2O3 composite nanoparticles of Example 2;
[0052] Figure 4 This is the XPS graph of the few-layer graphene-supported Ni / Sc2O3 composite nanoparticles of Example 2;
[0053] Figure 5This is the BET diagram of the few-layer graphene-loaded Ni / Sc2O3 composite nanoparticles of Example 2.
[0054] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] It should be noted that if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0057] In the examples of this application, the raw materials involved are all available in the market, wherein: the purity of the methanol is ≥99.9%, the nickel nitrate hexahydrate is analytically pure, the purity of the scandium nitrate hydrate is ≥99.9%, and the purity of the few-layer graphene is ≥99.9%. The examples of the present invention have no special requirements for the transition metal source, transition metal oxide source, and load material, and can all be implemented.
[0058] The embodiments of the present application can effectively control the morphology and size of the product, the process is simple, and the obtained product has high purity, good dispersibility of nanoparticles, uniform particle size and good catalytic activity.
[0059] Example 1
[0060] A metal / metal oxide composite catalyst comprises a support material and composite particles supported on the support material; the composite particles are particles made of a transition metal element and a transition metal oxide; based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the support material is 39.93%, the mass percentage of the transition metal element is 43.15%, and the mass percentage of the transition metal oxide is 16.92%.
[0061] The mass ratio of the transition metal element to the transition metal oxide is 2.55:1; the ratio of the sum of the masses of the transition metal element and the transition metal oxide to the mass of the support material is 3.55:2.36.
[0062] The load material is few-layer graphene (FLG); the transition metal element is metal nickel (Ni); the transition metal oxide is scandium trioxide (Sc2O3); and the composite particles are nano-composite particles.
[0063] The preparation method of the metal / metal oxide composite catalyst comprises the following steps:
[0064] SO1, add 0.8724g nickel nitrate hexahydrate powder and 0.249g scandium nitrate hydrate powder into 50mL methanol, stir until dissolved, and obtain a first mixed solution; add 0.7207g urea into the first mixed solution, stir until dissolved, and obtain a second mixed solution;
[0065] SO2, add 0.037g of ammonium fluoride (NH4F) and 0.163g of FLG to the second mixed solution, stir evenly, and obtain a third mixed solution;
[0066] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing (methanol washing) and drying it, then heat-treating it, and cooling it to obtain a metal / metal oxide composite catalyst (a few-layer graphene-loaded Ni / Sc2O3 composite nanocatalyst, i.e., Ni / Sc2O3@FLG catalyst).
[0067] In step SO1, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0068] In step SO2, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0069] In step SO3,
[0070] The temperature of the hydrothermal reaction is 120° C.; the time of the hydrothermal reaction is 8 hours.
[0071] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0072] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.
[0073] The drying temperature is 80° C. and the drying time is 24 h.
[0074] The heat treatment temperature is 500° C. (heated to 500° C. at a heating rate of 5° C. per minute); the heat treatment time is 1 h.
[0075] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0076] This embodiment also provides application of the metal / metal oxide composite catalyst in hydrogen storage materials.
[0077] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal / metal oxide composite catalyst.
[0078] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 92% of magnesium hydride and 8% of the metal / metal oxide composite catalyst.
[0079] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.
[0080] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 0.92g% magnesium hydride and 0.08g of the metal / metal oxide composite catalyst to obtain a mixed powder; and ball-milling the mixed powder to obtain the magnesium-based composite hydrogen storage material.
[0081] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal / metal oxide composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.
[0082] The prepared magnesium-based composite hydrogen storage material can adsorb 6.54wt% hydrogen within 10 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 6.59wt% hydrogen within 30 minutes at 573K.
[0083] Example 2
[0084] A metal / metal oxide composite catalyst comprises a support material and composite particles supported on the support material; the composite particles are particles made of a transition metal element and a transition metal oxide; based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the support material is 29.98%, the mass percentage of the transition metal element is 50.30%, and the mass percentage of the transition metal oxide is 19.72%.
[0085] The mass ratio of the transition metal element to the transition metal oxide is 2.55:1; the ratio of the sum of the masses of the transition metal element and the transition metal oxide to the mass of the support material is 3.55:1.52.
[0086] The load material is few-layer graphene (FLG); the transition metal element is metal nickel (Ni); the transition metal oxide is scandium trioxide (Sc2O3); and the composite particles are nano-composite particles.
[0087] The preparation method of the metal / metal oxide composite catalyst comprises the following steps:
[0088] SO1, add 0.8724g nickel nitrate hexahydrate powder and 0.249g scandium nitrate hydrate powder into 50mL methanol, stir until dissolved, and obtain a first mixed solution; add 0.7207g urea into the first mixed solution, stir until dissolved, and obtain a second mixed solution;
[0089] SO2, add 0.037g of ammonium fluoride (NH4F) and 0.105g of FLG to the second mixed solution, stir evenly to obtain a third mixed solution;
[0090] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing (methanol washing) and drying it, then heat-treating it, and cooling it to obtain a metal / metal oxide composite catalyst (a few-layer graphene-loaded Ni / Sc2O3 composite nanocatalyst, i.e., Ni / Sc2O3@FLG catalyst).
[0091] In step SO1, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0092] In step SO2, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0093] In step SO3,
[0094] The temperature of the hydrothermal reaction is 120° C.; the time of the hydrothermal reaction is 8 hours.
[0095] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0096] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.
[0097] The drying temperature is 80° C. and the drying time is 24 h.
[0098] The heat treatment temperature is 500° C. (heated to 500° C. at a heating rate of 5° C. per minute); the heat treatment time is 1 h.
[0099] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0100] This embodiment also provides application of the metal / metal oxide composite catalyst in hydrogen storage materials.
[0101] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal / metal oxide composite catalyst.
[0102] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 92% of magnesium hydride and 8% of the metal / metal oxide composite catalyst.
[0103] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.
[0104] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 0.92g% magnesium hydride and 0.08g of the metal / metal oxide composite catalyst to obtain a mixed powder; and ball-milling the mixed powder to obtain the magnesium-based composite hydrogen storage material.
[0105] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal / metal oxide composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.
[0106] The prepared magnesium-based composite hydrogen storage material can adsorb 6.66wt% hydrogen within 5 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 6.67wt% hydrogen within 30 minutes at 573K.
[0107] Figure 1 is the X-ray diffraction (XRD) pattern of the Ni / Sc2O3@FLG catalyst of this embodiment. Figure 1 It can be seen that the phase components of Ni / Sc2O3@FLG catalyst are metallic nickel and metal oxide scandium trioxide. Figure 2 The FESEM and EDS spectra of the Ni / Sc2O3@FLG catalyst of this embodiment are shown in FIG. Figure 2 Flower-shaped few-layer graphene can be seen in the image, and nanoparticles on the few-layer graphene are vaguely visible. Figure 3 TEM and EDS images of the Ni / Sc2O3@FLG catalyst of this embodiment. Figure 3 It can be seen that the ultrafine and highly dispersed Ni / Sc2O3 nanoparticles are evenly distributed on the few-layer graphene, and the element distribution of Ni and Sc is very uniform. Figure 4 This is the XPS graph of the Ni / Sc2O3@FLG catalyst of this embodiment. Figure 4The peaks of elemental nickel and nickel oxide can be seen in the graphene. The existence of Ni-C bonds indicates that the Ni / Sc2O3 particles have been successfully loaded on the few-layer graphene. Figure 5 The BET diagram of the Ni / Sc2O3@FLG catalyst of this embodiment shows that the specific surface area of the Ni / Sc2O3@FLG catalyst is 301.13 m 2 / g, and the average pore size is 7.92nm; the large specific surface area is conducive to the uniform dispersion of nanoparticles, and can better coat the magnesium hydride particles, thereby effectively preventing the agglomeration of nanoparticles.
[0108] In addition, the composite catalyst prepared in the embodiment of the present invention contains Ni / Sc2O3 nanoparticles. Figure 3 The scale data and particle size show that the Ni / Sc2O3 nanoparticles have excellent loading and dispersion properties on the few-layer graphene, with a small particle size and an average size of about 20nm. Figure 4 It can be seen from the XPS and other results that the Ni / Sc2O3 nanoparticles are firmly loaded on the few-layer graphene carrier, indicating that the Ni / Sc2O3 nanoparticles will not be separated from the few-layer graphene due to treatments such as centrifugation and ultrasound.
[0109] It can be seen that after appropriate hydrothermal reaction treatment and high-temperature heat treatment, the prepared Ni / Sc2O3@FLG catalyst has a very small particle size and is very evenly dispersed. After ball milling treatment, it can be well combined with magnesium hydride and has good performance.
[0110] Example 3
[0111] A metal / metal oxide composite catalyst comprises a support material and composite particles supported on the support material; the composite particles are particles made of a transition metal element and a transition metal oxide; based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the support material is 19.87%, the mass percentage of the transition metal element is 57.56%, and the mass percentage of the transition metal oxide is 22.57%.
[0112] The mass ratio of the transition metal element to the transition metal oxide is 2.55:1; the ratio of the sum of the masses of the transition metal element and the transition metal oxide to the mass of the support material is 3.55:0.88.
[0113] The load material is few-layer graphene (FLG); the transition metal element is metal nickel (Ni); the transition metal oxide is scandium trioxide (Sc2O3); and the composite particles are nano-composite particles.
[0114] The preparation method of the metal / metal oxide composite catalyst comprises the following steps:
[0115] SO1, add 0.8724g nickel nitrate hexahydrate powder and 0.249g scandium nitrate hydrate powder into 50mL methanol, stir until dissolved, and obtain a first mixed solution; add 0.7207g urea into the first mixed solution, stir until dissolved, and obtain a second mixed solution;
[0116] SO2, add 0.037g of ammonium fluoride (NH4F) and 0.061g of FLG to the second mixed solution, stir evenly, and obtain a third mixed solution;
[0117] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing (methanol washing) and drying it, then heat-treating it, and cooling it to obtain a metal / metal oxide composite catalyst (a few-layer graphene-loaded Ni / Sc2O3 composite nanocatalyst, i.e., Ni / Sc2O3@FLG catalyst).
[0118] In step SO1, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0119] In step SO2, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0120] In step SO3,
[0121] The temperature of the hydrothermal reaction is 120° C.; the time of the hydrothermal reaction is 8 hours.
[0122] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0123] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.
[0124] The drying temperature is 80° C. and the drying time is 24 h.
[0125] The heat treatment temperature is 500° C. (heated to 500° C. at a heating rate of 5° C. per minute); the heat treatment time is 1 h.
[0126] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0127] This embodiment also provides application of the metal / metal oxide composite catalyst in hydrogen storage materials.
[0128] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride and the metal / metal oxide composite catalyst.
[0129] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 92% of magnesium hydride and 8% of the metal / metal oxide composite catalyst.
[0130] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.
[0131] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 0.92g% magnesium hydride and 0.08g of the metal / metal oxide composite catalyst to obtain a mixed powder; and ball-milling the mixed powder to obtain the magnesium-based composite hydrogen storage material.
[0132] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal / metal oxide composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.
[0133] The prepared magnesium-based composite hydrogen storage material can adsorb 6.61wt% hydrogen within 5 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 6.51wt% hydrogen within 30 minutes at 573K.
[0134] Comparative Example 1
[0135] A few-layer graphene-supported Ni catalyst, wherein the mass ratio of metallic nickel to the few-layer graphene is 1.68:1, and the preparation method is as follows:
[0136] SO1, add 0.8724g nickel nitrate hexahydrate powder into 50mL methanol, stir until dissolved, and obtain a first mixed solution; add 0.7207g urea into the first mixed solution, stir until dissolved, and obtain a second mixed solution;
[0137] SO2, add 0.037g of ammonium fluoride (NH4F) and 0.105g of FLG to the second mixed solution, stir evenly to obtain a third mixed solution;
[0138] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing (methanol washing) and drying it, then heat treating it, and cooling it to obtain a few-layer graphene-supported Ni catalyst (i.e., Ni@FLG catalyst).
[0139] In step SO1, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0140] In step SO2, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0141] In step SO3,
[0142] The temperature of the hydrothermal reaction is 120° C.; the time of the hydrothermal reaction is 8 hours.
[0143] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0144] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.
[0145] The drying temperature is 80° C. and the drying time is 24 h.
[0146] The heat treatment temperature is 500° C. (heated to 500° C. at a heating rate of 5° C. per minute); the heat treatment time is 1 h.
[0147] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0148] The catalytic performance of the prepared few-layer graphene-loaded Ni catalyst was tested: 0.92 g of magnesium hydride powder and 0.08 g of few-layer graphene-loaded Ni catalyst were put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3 h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the sum of the masses of the few-layer graphene-loaded Ni catalyst) was 30:1, the rotation speed was 400 r / min, and a magnesium-based composite hydrogen storage material (magnesium hydride / few-layer graphene-loaded Ni catalyst material) was obtained.
[0149] The prepared magnesium-based composite hydrogen storage material can adsorb 5.75wt% hydrogen within 5 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 6.42wt% hydrogen within 30 minutes at 573K.
[0150] Comparative Example 2
[0151] A few-layer graphene-supported Sc2O3 catalyst, wherein the mass ratio of scandium trioxide to the few-layer graphene is 1:1.52, and the preparation method is as follows:
[0152] SO1, add 0.249g of hydrated scandium nitrate powder into 50mL of methanol, stir until dissolved, and obtain a first mixed solution; add 0.7207g of urea to the first mixed solution, stir until dissolved, and obtain a second mixed solution;
[0153] SO2, add 0.037g of ammonium fluoride (NH4F) and 0.105g of FLG to the second mixed solution, stir evenly to obtain a third mixed solution;
[0154] SO3, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing (methanol washing) and drying it, then heat-treating it, and cooling it to obtain a few-layer graphene-loaded Sc2O3 catalyst (i.e., Sc2O3@FLG catalyst).
[0155] In step SO1, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0156] In step SO2, the stirring is magnetic stirring; and the stirring time is 60 minutes.
[0157] In step SO3,
[0158] The temperature of the hydrothermal reaction is 120° C.; the time of the hydrothermal reaction is 8 hours.
[0159] The hydrothermal reaction is carried out in a hydrothermal reactor.
[0160] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.
[0161] The drying temperature is 80° C. and the drying time is 24 h.
[0162] The heat treatment temperature is 500° C. (heated to 500° C. at a heating rate of 5° C. per minute); the heat treatment time is 1 h.
[0163] The heat treatment is carried out in a tube furnace in a hydrogen atmosphere.
[0164] The catalytic performance of the prepared few-layer graphene-loaded Sc2O3 catalyst was tested: 0.92g of magnesium hydride powder and 0.08g of few-layer graphene-loaded Sc2O3 catalyst were put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the sum of the masses of the Sc2O3 catalyst loaded with few-layer graphene) was 30:1, the rotation speed was 400r / min, and a magnesium-based composite hydrogen storage material (magnesium hydride / few-layer graphene-loaded Sc2O3 catalyst material) was obtained.
[0165] The prepared magnesium-based composite hydrogen storage material can adsorb 4.58 wt% hydrogen within 5 minutes at a hydrogen pressure of 3.0 MPa and 473 K, and can release 5.17 wt% hydrogen within 30 minutes at 573 K.
[0166] Comparative Example 3
[0167] 1.00 g of magnesium hydride powder was put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3 h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder) was 30:1, and the rotation speed was 400 r / min to obtain pure magnesium hydride powder.
[0168] The above pure magnesium hydride can absorb 1.36 wt% hydrogen in 5 min at 3.0 MPa hydrogen pressure and 473 K, and can release 1.54 wt% hydrogen in 30 min at 573 K. It can be seen that the hydrogen absorption and desorption performance of pure magnesium hydride is very poor without adding any catalyst.
[0169] From the above examples, it can be seen that for Comparative Example 1, when a few-layer graphene-supported metal nickel catalyst material is added alone, the introduction of metal nickel can accelerate the charge transfer between magnesium and hydrogen in magnesium hydride; for Comparative Example 2, when a few-layer graphene-supported scandium trioxide catalyst material is added alone, the introduction of scandium trioxide can destroy the passivation layer on the particle surface and generate an activated substance Sc0, thereby improving the hydrogen storage performance of magnesium hydride. However, the hydrogen absorption and desorption performance of Comparative Examples 1-2 is still worse than that of the embodiments of the present invention.
[0170] The mechanism of the catalytic effect of Examples 1-3 of the present invention being stronger than that of Comparative Examples 1-2 is explained as follows: For Examples 1-3, when a composite catalyst of metal nickel and scandium trioxide supported by a few-layer graphene is added to magnesium hydride, its hydrogen absorption and desorption performance is further improved compared with Comparative Examples 1-2, because there is a significant synergistic catalytic effect between Ni and Sc2O3, thereby achieving a complementary effect. This synergistic effect can greatly improve the hydrogen absorption and desorption performance of magnesium hydride, which is more advantageous than a single-phase catalyst.
[0171] It can be seen that the composite catalysts of Examples 1-3 can all achieve rapid hydrogen absorption and desorption performance, and have significantly better performance data than the comparative examples. In the examples of the present application, the amount of the supported material needs to be controlled; too much supported material few-layer graphene will reduce the content of the catalytic material, thereby affecting the catalytic performance of the catalyst, and further reducing the hydrogen storage capacity of the magnesium-based composite material; if the supported material few-layer graphene is too little, the supported nanoparticles cannot be well dispersed, and the catalytic material is easily agglomerated, thereby reducing the catalytic performance of the catalyst, and causing the magnesium-based composite hydrogen storage material to exhibit slightly poor hydrogen absorption and desorption performance.
[0172] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A metal / metal oxide composite catalyst, characterized in that: The invention comprises a support material and composite particles supported on the support material; the composite particles are particles made of a transition metal element and a transition metal oxide; based on the mass of the metal / metal oxide composite catalyst being 100%, the mass percentage of the support material is 10% to 80%, the mass percentage of the transition metal element is 10% to 45%, and the mass percentage of the transition metal oxide is 10% to 45%; The load material is few-layer graphene; the transition metal element is nickel; the transition metal oxide is scandium trioxide; and the composite particles are nanocomposite particles; The preparation method of the metal / metal oxide composite catalyst comprises the following steps: S01, adding a transition metal source and a transition metal oxide source to an organic solvent, stirring until dissolved, to obtain a first mixed solution; adding urea to the first mixed solution, stirring until dissolved, to obtain a second mixed solution; S02, adding ammonium fluoride and a supporting material to the second mixed solution, stirring evenly, to obtain a third mixed solution; S03, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing and drying it, and then subjecting it to a heat treatment and cooling it to obtain a metal / metal oxide composite catalyst.
2. The metal / metal oxide composite catalyst according to claim 1, characterized in that: The mass ratio of the transition metal element to the transition metal oxide is (1-3):(1-3); the ratio of the sum of the masses of the transition metal element and the transition metal oxide to the mass of the support material is (0.5-9):
1.
3. The method for preparing the metal / metal oxide composite catalyst according to claim 1, characterized in that: The steps include: S01, adding a transition metal source and a transition metal oxide source to an organic solvent, stirring until dissolved, to obtain a first mixed solution; adding urea to the first mixed solution, stirring until dissolved, to obtain a second mixed solution; S02, adding ammonium fluoride and a supporting material to the second mixed solution, stirring evenly, to obtain a third mixed solution; S03, subjecting the third mixed solution to a hydrothermal reaction to obtain a reaction product; centrifuging the reaction product, taking a precipitate, washing and drying it, and then subjecting it to a heat treatment and cooling it to obtain a metal / metal oxide composite catalyst.
4. The method for preparing the metal / metal oxide composite catalyst according to claim 3, characterized in that: In step S01, 0.8724 g of nickel source was added to every 50 ml of organic solvent; the mass ratio of the nickel source to the urea was 1.2105:1; The transition metal element source is nickel nitrate hexahydrate; The transition metal oxide source is hydrated scandium nitrate; The organic solvent is methanol; In step S02, The mass ratio of the ammonium fluoride to the support material is 1:(1.649-4.406); The support material is few-layer graphene; The stirring is magnetic stirring; the stirring time is 20 min to 60 min.
5. The method for preparing the metal / metal oxide composite catalyst according to claim 3, characterized in that: In step S03, The temperature of the hydrothermal reaction is 100°C to 180°C, and the time of the hydrothermal reaction is 5h to 15h; The centrifugal speed is 5000 r / min to 8000 r / min, and the centrifugal time is 5 min to 20 min; The drying temperature is 50°C to 80°C, and the drying time is 20 h to 48 h; The temperature of the heat treatment is 400°C to 800°C, and the time of the heat treatment is 0.5 h to 5 h.
6. Use of the metal / metal oxide composite catalyst according to claim 1, characterized in that: The metal / metal oxide composite catalyst is used in hydrogen storage materials, hydrolysis hydrogen production materials, battery materials, super capacitors and photoelectric materials.
7. Use of the metal / metal oxide composite catalyst according to claim 6, characterized in that: The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride and the metal / metal oxide composite catalyst.
8. Use of the metal / metal oxide composite catalyst according to claim 7, characterized in that: Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 80% to 99% of magnesium hydride and 1% to 20% of the metal / metal oxide composite catalyst.
9. Use of the metal / metal oxide composite catalyst according to claim 8, characterized in that: The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 80% to 99% of magnesium hydride and 1% to 20% of the metal / metal oxide composite catalyst to obtain a mixed powder; ball milling the mixed powder to obtain a magnesium-based composite hydrogen storage material; The ball-to-material ratio of the ball mill is (10-50):1; the ball milling time is 1 h-10 h; the rotation speed of the ball mill is 200 r / min-500 r / min; and the ball milling is carried out in an inert atmosphere.